Assessment of cattle welfare on Ghanaian farms - Mogre, Joshua; Adzitey, Frederick; Teye, Gabriel (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2021)
The objective of the study was to assess farm welfare conditions and the observance of welfare by cattle farmers in Ghana. The study applied field approaches to gather and analyze data. Data was collected from farms in the Northern, North East and Savanna regions. A total of three hundred and eighteen (318) cattle farmers were interviewed using semi-structured questionnaire. Observations and focus group discussions were also used to obtain data or verify some of the responses from the cattle farmers. Data collected was classified and summarized on the basis of the information provided. The study found evidence that most farmers were concerned about their animal’s welfare, but did not place equal weight on the five freedoms of animal welfare. Farmers placed the most premium on freedom from hunger, malnutrition and thirst (95%), and freedom from pain, injury and disease (90%). Farmers placed less premium on their animals freedoms from fear and distress (50%), and freedom from physical and thermal discomfort (50%). The freedom to express normal patterns of behaviour (0%) was not considered by the farmers. Observance of animal welfare by cattle farms was relatively below acceptable standards and government interventions are needed to improve animal welfare in Ghana.